The asymmetric effects of weather shocks on euro area inflation - Matteo Ciccarelli; Friderike Kuik; Catalina Martínez Hernández (European Central Bank (ECB), 2023)
This paper assesses the impact of weather shocks on inflation components in the four largest euro area economies. We combine high-frequency weather data with monthly data on inflation and output growth within a set of Bayesian Vector Autoregressions which explicitly considers the seasonal dependence of the shock. Results suggest the presence of significant country asymmetries and seasonal responses of inflation to temperature shocks, mainly via food, energy, and service prices. An increase in monthly mean temperatures has inflationary effects in summer and autumn, with a stronger response in warmer euro area countries. An increase in temperature variability has significant upward impacts on inflation rates over and above the impacts of changes in means.
Keywords: Q54; E31; C32; 330; Temperature shocks; Climate change; Inflation; Vector Autoregression